1997
DOI: 10.1111/j.1471-0528.1997.tb11493.x
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical artery Doppler velocimetry in unselected and low risk pregnancies: a review of randomised controlled trials

Abstract: Objective Meta-analysis of data from controlled trials performed in populations at high risk have shown that umbilical artery Doppler velociinetry (umbilical Doppler) can reduce perinatal mortality. The individual published trials among unselected or low risk populations have found no beneficial effect. Our objective was to evaluate the effect of routine use of the umbilical Doppler in unselected or low risk pregnancies by reviewing all published and unpublished randomised controlled trials.Study design System… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 14 publications
1
18
0
2
Order By: Relevance
“…[1] It has been studied that Doppler velocimetry of umbilical artery in unselected and low-risk pregnancies cannot be recommended. [2] In contrast, it has been proved by many studies that Doppler has a very important role in screening of high-risk pregnancies. [3][4][5] Abnormal fetal circulation is considered a major factor in fetal growth restriction, both as a cause and an indicator.…”
Section: Introductionmentioning
confidence: 99%
“…[1] It has been studied that Doppler velocimetry of umbilical artery in unselected and low-risk pregnancies cannot be recommended. [2] In contrast, it has been proved by many studies that Doppler has a very important role in screening of high-risk pregnancies. [3][4][5] Abnormal fetal circulation is considered a major factor in fetal growth restriction, both as a cause and an indicator.…”
Section: Introductionmentioning
confidence: 99%
“…Few interventions exist to prevent FGR, but the surveillance of growth‐restricted fetuses makes it possible to induce delivery in order to avoid severe fetal compromise or death. Antenatal monitoring includes umbilical artery Doppler velocimetry, allowing for a 30% reduction in perinatal mortality in high‐risk pregnancies …”
Section: Introductionmentioning
confidence: 99%
“…These findings have been further confirmed by a Cochrane review on fetal and umbilical Doppler scans in high‐risk pregnancies16. In unselected and low‐risk populations the previously published evidence has not supported the routine use of umbilical artery Doppler12, 13. One test accuracy study looked at the use of intrapartum umbilical artery Doppler and concluded that it was a poor predictor of adverse outcome49.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews have reported varying results11–15, the most striking originating from a series of reviews of randomized controlled trials (RCT) in high‐risk populations, in which an association with Doppler ultrasound and a reduction in perinatal deaths (risk ratio = 0.71; 95% CI, 0.52–0.98) was demonstrated16. There was also an association with fewer instances of induction of labor (risk ratio = 0.89; 95% CI, 0.80–0.99) and fewer Cesarean sections (risk ratio = 0.90; 95% CI, 0.84–0.97).…”
Section: Introductionmentioning
confidence: 99%